Intervensi Senam Aerobic Low Impact Sebagai Upaya Mengontrol Halusinasi Pendengaran: Studi Kasus - Gunawan Gunawan; suhariyanto SUHARIYANTO S.Kep. suhariyanto; Lily Yuniar (PENA NURSING, 2023)
On January 16, 2023, it was recorded that 64 mental patients were treated in the Walet room at the Mental Hospital in West Kalimantan Province, out of 64 people, 47 people with mental disorders had auditory hallucinations. Management of clients with auditory hallucinations. it is very important to avoid the consequences such as injuring yourself, others and the environment. In the swallow room, management has been carried out with several interventions, namely Implementation Strategy (1), namely helping clients get to know hallucinations, content, time, frequency, situations that cause hallucinations and responses. Implementation Strategy (2) Practice controlling hallucinations by scolding. Implementation Strategy (3) Evaluation of SP2, Train clients how to control hallucinations by conversing with other people. Implementation Strategy (4) Evaluation of SP2 and SP3 Practice controlling hallucinations by carrying out scheduled activities. Implementation Strategy (5) Evaluation of SP2, SP3 and SP4. Practice controlling hallucinations by taking medication and include all interventions in the daily activity schedule. In the fourth implementation strategy (4), namely training to control hallucinations by carrying out scheduled activities, it is necessary to add proper management, namely by increasing group activities so that they return to perceptions that are in accordance with reality. One of them is by doing physical activities such as low impact aerobics. One effort to overcome this is to make patients with auditory hallucinations have activities that reduce the stimulus for the appearance of hallucinations, one of which is by doing low impact aerobic exercise. The aim of the care given is to apply low impact aerobic exercise to clients of auditory hallucinations in the Swallow Room of the West Kalimantan Provincial Mental Hospital in 2023. The patient's initials are Mr. MA, 27 years old, was admitted to the hospital because she was often angry, her emotions were out of control, she often broke things, and the client had slashed her friend. While being treated, the patients said that someone was whispering in his ear, and there was a sword accompanying him. The results of implementing the low impact aerobic exercise intervention for three times a week showed that the frequency of hallucinations decreased. Low impact aerobic exercise can be performed as an additional intervention to increase the activity of patients with hallucinations. Low impact aerobics can be applied to fill in the scheduled activities of patients with auditory hallucinations